Level of winter protein supplementation for steer calves both wintered and summer grazed on bluestem pasture. - Smith, E.F.; Koch, B.A.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
This is the third trial of this experiment. In addition to this year's test, a three-year summary is included in this circular. The test is designed to study the level of protein supplementation most desirable for wintering steer calves on dry bluestem pasture that are to be sold off summer grass as stocker or feeder yearlings. Results of this test are measured primarily by the combined winter and summer performance of the steers.
Keywords: Beef; Protein; Winter grazing; Summer grazing; Bluestem pasture